Planning and Conceptualizing Crispy Tofu Packaging Design Using Kansei Engineering Method - Novi Purnama Sari; Mohamad Rifai; Kayla Putri Sagita; Rinda Ayu Febriyanti (Industrial Engineering Study Program, Faculty of Engineering, Universitas Sebelas Maret (UNS), 2026)
Indonesian society has long consumed tofu as a side dish or snack. A crucial issue identified in the packaging of Tahu Crispy is the use of non-food-grade duplex paper, which absorbs excessive oil, lacks product identity, and has an unattractive design. Therefore, this study aims to determine a suitable packaging design concept for Tahu Crispy. The Kansei Engineering method is employed due to its ability to interpret consumer impressions, emotions, and desires. The Kansei words were grouped using Principal Component Analysis (PCA). A total of 31 Kansei words were obtained through a questionnaire distributed with video stimuli. The data was then processed using R software, generating a design concept based on PCA input.